Pengaruh Profesionalisme Guru Pendidikan Agama Islam Terhadap Pelaksanaan Model Pembelajaran Online di SMAN 1 Pangkalpinang - Dicky Ruchyat Shidik; Aulia Fitri; Zulkipli Lessy (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
The problem in this study was taken based on the conditions of the world of education that changed the learning process to online or online, namely online learning that is not carried out face-to-face and replaced, due to the Covid-19 pandemic. A teacher, especially an Islamic religious education teacher, certainly experiences many difficulties and obstacles during the learning process. In this online learning process, there are still many students who do not understand thoroughly, especially in the Fiqh material because a demonstration method is needed. In addition, there are obstacles to the signal experienced by the teacher. Even though there are obstacles, learning must still be carried out to meet educational needs. Thus, the purpose of this study is to determine the effect of the professionalism of Islamic religious education teachers on the implementation of the online learning model during the Covid-19 pandemic at SMA N 1 Pangkalpinang. Using quantitative research with simple linear regression analysis, the results of this study indicate that there is a significant influence of the professionalism of Islamic religious education teachers on the online learning model during the Covid-19 pandemic at SMA N 1 Pangkalpinang. The results of the data analysis obtained a t-value of 6.855, while the t table with n = 102 significant level of 0.05 is 1.660 meaning t count> t table, 6.855> 1.660. It can be concluded that Ho is rejected and Ha is accepted. The results of the simple linear regression equation, namely Y = 32.818 + 0.436X, are positive. The large contribution of the influence of the professionalism of Islamic religious education teachers on the online learning model is 32% and 68% is influenced by other factors. Abstrak Permasalahan dalam penelitian ini diambil berdasarkan kondisi dunia pendidikan yang merubah proses pembelajaran menjadi dalam jaringan atau daring yaitu pembelajaran online yang tidak dilakukan secara tatap muka dan digantikan, karena terjadi pandemi Covid-19. Seorang guru terkhusus guru pendidikan agama Islam tentunya banyak mengalami kesulitan dan hambatan saat proses pembelajaran berlangsung. Dalam proses pembelajaran online ini masih banyak ditemukan peserta didik yang tidak paham secara menyeluruh khususnya pada materi Fiqih karena perlu metode demonstrasi. Selain itu, kendala pada sinyal yang dialami oleh guru. Walaupun terdapat hambatan pembelajaran harus tetap dilaksanakan untuk memenuhi kebutuhan pendidikan. Dengan begitu tujuan dari penelitian ini adalah untuk mengetahui pengaruh profesionalisme guru pendidikan agama Islam terhadap pelaksanaan model pembelajaran online era pandemi Covid-19 di SMA N 1 Pangkalpinang. Menggunakan penelitian kuantitatif dengan analisis regresi linier sederhana. Hasil penelitian ini menunjukkan ada pengaruh yang signifikan profesionalisme guru pendidikan agama Islam terhadap model pembelajaran online era pandemi Covid-19 di SMA N 1 Pangkalpinang. Hasil analisis data memperoleh nilai t hitung sebesar 6.855, sedangkan t tabel dengan n= 102 taraf signifikan 0,05 adalah 1.660 berarti t hitung > t tabel, 6.855 > 1.660. Dapat ditarik kesimpulan Ho ditolak dan Ha diterima. Hasil persamaan regresi linier sederhana yaitu Y=32,818+0,436X bernilai positif. Besar kontribusi pengaruh profesionalisme guru pendidik agama Islam terhadap model pembelajaran online sebesar 32% dan 68% dipengaruhi oleh faktor lain.